Laju Pertumbuhan Tanaman krisan (Crhysantemum) pada Pemberian Tambahan Cahaya Lampu LED (Light Emitting Diode) Kombinasi Warna Merah-Biru dengan Metode Siklik - Ni Wayan Anik Wahyuni; I Made Anom Sutrisna Wijaya; I Made Nada (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
Chrysantemum cultivation in tropical region like Indonesia required the provision of additional light..The application of additional light is done by using artificial light from electric lamp in the evening for 4 hours after the sun set. This research determine the best cyclic pattern to generate the highest growth rate. The application that had been given in this research was the addition of LED lights of red-blue combination in a cyclic (off, on, off). Cyclic number given is 1 cycle, 2 cycles, 3 cycles, 4 cycles, 5 cycles and controls. The collected data were analyzed by regression analysis. The variables observed is plant height, the leaves number, the canopy area, and the rod diameter. The result showed that the addition of LED lights of red-blue combination for one cycle gave the best impact for rate of growth of chrysanthemum plant. The addition of LED red-blue combination one cycle gave the best effect against chrysanthemum plant growth, which was showed produced the highest growth rate of plant height (y = 1.106x + 2.11), the leaves number (y = 0.514x + 3.163), the canopy area (y = 2.346x + 21.61), and the rod diameter ((y = 0.082x + 0.168).